Epitaxy on Demand. (14th July 2015) - Nijland, Maarten; Thomas, Sean; Smithers, Mark A.; Banerjee, Nirupam; Blank, Dave H. A.; Rijnders, Guus; Xia, Jing; Koster, Gertjan; ten Elshof, Johan E.
Abstract : Perovskite oxide heteroepitaxy is realized on the top of inorganic nanosheets that are covering the amorphous oxide surfaces of Si substrates. Utilizing pulsed laser deposition, thin films of SrRuO3 in a (001)pc and (110)pc orientation on nanosheets of Ca2 Nb3 O10 and Ti0.87 O2 are grown, respectively. The two types of nanosheets are patterned to locally tailor the crystallographic orientation and properties of SrRuO3 . The success of our approach is demonstrated by electron backscatter diffraction and spatial magnetization maps. An unprecedented control of perovskite film growth on arbitrary substrates is illustrated in this work, and the methods that are developed to deposit SrRuO3 thin films are a viable starting point for growth of artificial heteroepitaxial thin films that require a bottom electrode. Control is not just reached in the direction of film growth, as the crystal orientation and film properties are regulated laterally on the surface of micropatterned nanosheets. Local control of magnetic properties is illustrated, which holds out prospects for the fabrication of next‐generation devices like noncollinear magnetic random access memories. Abstract : Perovskite thin films are deposited on Si substrates covered with inorganic nanosheets of Ca2 Nb3 O10 or Ti0.87 O2 . These nanosheets are used to control the nucleation of films that consist of a SrTiO3 buffer layer and a SrRuO3 top layer. The two types of nanosheets are micropatterned to locally tailor the crystallographic orientation, allowing lateral control of the magnetic properties of SrRuO3 .